The Social Foundations for Developing the Arabic Language Curriculum According to Ahmad Fuad Effendy - abul Ma'ali; Faisal Mahmoud Adam Ibrahim; Syuhadak Syuhadak (Ijaz Arabi Journal of Arabic Learning, 2022)
AbstractThe curriculum has laid a strategic position in the education process as it is the basis of the education process system. Ahmad Fuad Effendy is one of the leading Arabic language teaching activists who have a great effort in deploying and renewing Arabic teaching in Indonesia. He is the founder of the Federation of Arabic Language Teachers a member of the Board of Trustees of the King Abdullah bin Abdulaziz International Center for Arabic Language and has a long experience in the field of Arabic teaching. This study aims to raise the perspective of Ahmad Fuad Effendy in the social foundation in the Arabic curriculum because it is considered a basis that is very concerned when developing an educational curriculum. Researchers use a qualitative approach with biographical study techniques. The data was taken from articles and books written by Ahmad Fuad Effendy both in Arabic and Indonesian in the development of Arabic teaching curriculum and from interviews. Data analysis was carried out through 1) data condensation, 2) data presentation, and 3) withdrawal and verification of conclusions. The researchers came to the conclusion that analyzing the needs of the community and employment in Arabic language and literature was important when developing a curriculum, especially to formulate curriculum goals to increase the effectiveness of the curriculum.يحتل المنهج موقعاً استراتيجياً في العملية التعليمية لأنه أساس منظومة العملية التعليمية. أحمد فؤاد أفندي أحد ناشطي تعليم اللغة العربية البارزين الذين لديهم جهد كبير في نشر تعليم اللغة العربية وتجديد مساره في إندونيسيا. كان مؤسسا لاتحاد مدرسي اللغة العربية في إندونيسيا (IMLA) وعضوا لمجلس أمناء مركز الملك عبد الله بن عبد العزيز الدولي وله خبرة طويلة في مجال منهج تعليم اللغة العربية. هدف هذا البحث إبراز أفكار أحمد فؤاد أفندي في الأسس الاجتماعية لأنها تعتبر الأسس التي اهتم بها كثيرا عند تطوير منهج التعليم. اعتمد الباحثون هذا البحث على المدخل الكيفي على نوع السيرة باستخدام المدخل الموضوعي.  صدرت البيانات من المقالات والكتب التي كتبها أحمد فؤاد أفندي في منهج تعليم اللغة العربية والمقابلة. وتم تحليلها حسب رأي ميلس وهوبرمن وسلدانا: 1) تكثيف البيانات، 2) عرض البيانات وتحليلها و3) الاستنتاج والتحقق. توصل الباحثون إلى النتيجة أن تحليل متطلبات المجتمع ومجالات الأعمال في اللغة العربية وآدابها أمر مهم عند تطوير منهج دراسي خاصة لصياغة أهداف المنهج ويزيد فعالية المنهج.